Pengembangan Bahan Ajar Berbasis Teks al-Barzanjī untuk Peningkatan Hasil Belajar Bahasa Arab Siswa - Nurlatifah; Abdurrahman, Maman; Nursyamsiah, Nunung (Al-Ma‘rifah, 2022)
This research is motivated by low understanding of students at Al-Barokah Islamic boarding school, Bandung, in the knowledge of al-Barzanjī text on Madārij al-Ṣu‘ūd book. Therefore, using a stylistic analysis approach, the researcher developed Madārij al-Ṣu‘ūd teaching materials with al-Barzanjī text teaching materials. The method used in this research is Research and Development with ADDIE model. This study aimed to determine: (1) the steps for developing teaching materials; (2) the results of the field trial of teaching materials. Based on the study results, it can be seen: (1) the average result of the pretest for the experimental class is 48.33, and the control class is 50.83; (2) the average post-test result for the experimental class was 86.66, and the control class was 59.16; (3) the results of the N-Gain Score test showed an increase in the experimental class of 0.73 in the high category. In comparison, the increase produced by the control class is 0.12 in the low category. In conclusion, developing Fatḥ al-Bayān as a teaching material can improve students' understanding of the al-Barzanjī text. Therefore, the Arabic language skills possessed by students are increasing.